Memoria de una antropología de campo : Chinchero - Esteva Fabregat, Claudio (Revista Española de Antropología Americana, 2003)
This paper presents an epistemological review of fieldwork undertaken in Chinchero (Cuzco) in the summers of 1969 to 1971. It raises questions regarding linguistic problems posed by communication between anthropologist and Indian people through bilingual informants. Furthermore, it highlights the fact that seasonal fieldwork gives rise to certain personal cognitive limitations, because in the absence of personal observation, information has to be obtained from bilingual informants through the conducting of intensive oral questionnaires.